Ketamine as an adjuvant in sympathetic blocks for management of central sensitization following peripheral nerve injury - Sunder, Rani A; Toshniwal, Gokul; Dureja, GP (Journal of Brachial Plexus and Peripheral Nerve Injury, 2008)
Proliferation of NMDA receptors and role of glutamate in producing central sensitization and ’wind up’ phenomena in CRPS [complex regional pain syndrome] forms a strong basis for the use of Ketamine to block the cellular mechanisms that initiate and maintain these changes. In this case series, we describe 3 patients of CRPS Type II with debilitating central sensitization, heat/mechano allodynia and cognitive symptoms that we termed ’vicarious pain’. Each of these patients had dramatic relief with addition of Ketamine as an adjuvant to the sympathetic blocks after conventional therapy failed.Case Reports All 3 patients suffered gunshot wounds and developed characteristic features of CRPS Type II. Within 2–3 weeks they developed extraterritorial symptoms typical of central sensitization. The generalized mechanical allodynia and debilitating heat allodynia described to be rare in human subjects had life altering affect on their daily life. Case 2 and 3 also described an unusual cognitive phenomenon i.e. visual stimuli of friction would evoke severe pain in the affected limb that we have termed as ’vicarious pain’. They responded positively to sympathetic blocks but the sympatholysis did not bring relief to the heat and mechanical allodynia. Addition of Ketamine 0.5 mg/kg to the sympathetic blocks elicited resulted in marked relief in the allodynia.Conclusion Ketamine has a special role in patients with debilitating heat allodynia and positive cognitive symptoms via its action on central pain pathway. As an adjuvant in sympatholytic blocks it has a targeted action without significant neuropsychiatric side effects.